MMS observations of ion‐scale magnetic island in the magnetosheath turbulent plasma. Issue 15 (14th August 2016) - Huang, S. Y.; Sahraoui, F.; Retino, A.; Le Contel, O.; Yuan, Z. G.; Chasapis, A.; Aunai, N.; Breuillard, H.; Deng, X. H.; Zhou, M.; Fu, H. S.; Pang, Y.; et al.
Abstract: In this letter, first observations of ion‐scale magnetic island from the Magnetospheric Multiscale mission in the magnetosheath turbulent plasma are presented. The magnetic island is characterized by bipolar variation of magnetic fields with magnetic field compression, strong core field, density depletion, and strong currents dominated by the parallel component to the local magnetic field. The estimated size of magnetic island is about 8 di, where di is the ion inertial length. Distinct particle behaviors and wave activities inside and at the edges of the magnetic island are observed: parallel electron beam accompanied with electrostatic solitary waves and strong electromagnetic lower hybrid drift waves inside the magnetic island and bidirectional electron beams, whistler waves, weak electromagnetic lower hybrid drift waves, and strong broadband electrostatic noise at the edges of the magnetic island. Our observations demonstrate that highly dynamical, strong wave activities and electron‐scale physics occur within ion‐scale magnetic islands in the magnetosheath turbulent plasma. Key Points: Ion‐scale magnetic island is identified in the magnetosheath Electron beams and intense wave emissions in the magnetic island Multiscale coupling occurs in magnetic island